A controlled experiment investigation of understandability and correctness on two query languages for XML data. (1st January 2013) - Keramopouloss, Euclid; Deligiannis, Ignatios; Spanos, Georgios; Pliakas, Achilleas; Tsekos, Konstantinos
The study presented in this paper is a controlled experiment, aiming at investigating the understandability and correctness in two query languages, namely KINISIS against XQuery. XQuery is the W3C standard query language for XML documents. KINISIS is a graphical query language which is designed and implemented upon XQuery, using metaphors extracted from the European Road Traffic Act. We conducted a controlled experiment in order to assess users' performance, with respect to understanding and correctness, in developing queries in KINISIS and in XQuery. The findings, from the collected and statistically analysed data, showed that users performing on KINISIS had significantly better results comparing to those using XQuery. As an output of this study, is that a graphical XQuery language that is based on successful metaphors is more appropriate for novice users in XQuery technology, instead of textual XQuery.